The Multi‐Kinase Inhibitor GZD824 (Olverembatinib) Shows Pre‐Clinical Efficacy in Endometrial Cancer - Dongli Liu; Dylan Glubb; Tracy O'Mara; Caroline E. Ford (Cancer Medicine)
ABSTRACT Objective Endometrial cancer is one of the few cancers for which mortality is still increasing. A lack of treatment options remains a major challenge, particularly for some subtypes of the disease. GZD824, also known as olverembatinib, is a multi‐kinase inhibitor previously investigated in clinical trials for chronic myeloid leukaemia and Ph+ acute lymphoblastic leukaemia as a BCR‐ABL inhibitor. This study aimed to investigate the pre‐clinical efficacy of GZD824 for the treatment of EC. Methods Here, we undertook pre‐clinical evaluation of GZD824 in seven endometrial cancer cell lines (HEC‐1‐A, HEC‐1‐B, MFE296, RL95‐2, Ishikawa, KLE and ARK‐1), one normal immortalised endometrium derived cell line (E6E7hTERT) and primary mesothelial and fibroblast cells isolated from normal omentum samples. Results GZD824 inhibited the proliferation of all endometrial cancer cell lines, which were significantly more sensitive to GZD824 compared to normal cells (p = 0.030). GZD824 significantly inhibited migration in Ishikawa (endometrioid) and ARK1 (serous) endometrial cancer cell lines and significantly inhibited invasion in the ARK1 cells. Whole transcriptome regulation following two doses (0.1 and 1 μM) of GZD824 in Ishikawa and ARK1 cells was investigated via RNA‐seq, and key components of enriched pathways were investigated at the translational level. Key pathways altered included ROR1/Wnt, GCN2‐ATF4, epithelial to mesenchymal transition (EMT) and PI3K‐AKT. Conclusion Together, these studies support further investigation of GZD824 as a potential therapeutic agent in endometrial cancer, potentially in combination with immune checkpoint inhibitors.